Experimental investigation on the anti-detonation performance of composite structure containing foam geopolymer backfill material - Hang Zhou; Hujun Li; Zhen Wang; Dongming Yan; Wenxin Wang; Guokai Zhang; Zirui Cheng; Song Sun; Mingyang Wang (Defence Technology)
The compression and energy absorption properties of foam geopolymers increase stress wave attenuation under explosion impacts, reducing the vibration effect on the structure. Explosion tests were conducted using several composite structure models, including a concrete lining structure (CLS) without foam geopolymer and six foam geopolymer composite structures (FGCS) with different backfill parameters, to study the dynamic response and wave dissipation mechanisms of FGCS under explosive loading. Pressure, strain, and vibration responses at different locations were synchronously tested. The damage modes and dynamic responses of different models were compared, and how wave elimination and energy absorption efficiencies were affected by foam geopolymer backfill parameters was analyzed. The results showed that the foam geopolymer absorbed and dissipated the impact energy through continuous compressive deformation under high strain rates and dynamic loading, reducing the strain in the liner structure by 52% and increasing the pressure attenuation rate by 28%. Additionally, the foam geopolymer backfill reduced structural vibration and liner deformation, with the FGCS structure showing 35% less displacement and 70% less acceleration compared to the CLS. The FGCS model with thicker, less dense foam geopolymer backfill, having more pores and higher porosity, demonstrated better compression and energy absorption under dynamic impact, increasing stress wave attenuation efficiency. By analyzing the stress wave propagation and the compression characteristics of the porous medium, it was concluded that the stress transfer ratio of FGCS-ρ-579 was 77% lower than that of CLS, and the transmitted wave energy was 90% lower. The results of this study provide a scientific basis for optimizing underground composite structure interlayer parameters.